2022
DOI: 10.25122/jml-2022-0087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 pandemic on a general surgery clinic

Abstract: The Covid-19 pandemic has had a massive impact on global health, social and economic well-being worldwide. In addition to the direct effects of the disease on patients infected with the virus, this pandemic has severely affected the activity of surgical clinics around the world. One of the significant issues was an important decrease in the number of surgeries performed even in countries with highly performant medical systems. This study aimed to analyze the effects of the pandemic on the 1st General Surgery C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, there is a significant emphasis on minimizing the risk of SARS-CoV-2 transmission, which necessitates shorter hospital stays to reduce patient exposure. 26 By reducing the duration of hospitalization, the potential for viral transmission is mitigated, benefiting both patients and healthcare workers. 27 These changes exemplify the evolving landscape of healthcare delivery in response to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a significant emphasis on minimizing the risk of SARS-CoV-2 transmission, which necessitates shorter hospital stays to reduce patient exposure. 26 By reducing the duration of hospitalization, the potential for viral transmission is mitigated, benefiting both patients and healthcare workers. 27 These changes exemplify the evolving landscape of healthcare delivery in response to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…First, hospitals encountered immense pressure during the peak of the COVID‐19 pandemic, prompting the implementation of strategies to expedite patient discharges after surgeries and increase bed availability. Moreover, there is a significant emphasis on minimizing the risk of SARS‐CoV‐2 transmission, which necessitates shorter hospital stays to reduce patient exposure 26 . By reducing the duration of hospitalization, the potential for viral transmission is mitigated, benefiting both patients and healthcare workers 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all physicians, surgical physicians come first in terms of risk. 11 Studies have shown 5,22,23 that most of the deaths caused by COVID-19 are among those working in surgical clinics. For this reason, it is understandable that sur-gical assistants with little experience and high workload are afraid of COVID-19.…”
Section: Discussionmentioning
confidence: 99%